Tumor Customized 2D Supramolecular Nanodiscs for Ultralong Tumor Retention and Precise Photothermal Therapy of Highly Heterogeneous Cancers (Small 21/2022). Issue 21 (26th May 2022) - Lin, Peng; Xue, Yucheng; Mu, Xueluer; Shao, Youyou; Lu, Qian; Jin, Xiangang; Yinwang, Eloy; Zhang, Zengjie; Zhou, Hao; Teng, Wangsiyuan; Sun, Hangxiang; Chen, Weida; et al.
Abstract : Photothermal Therapy In article number 2200179, Xuesheng Jiang, Xiaohua Yu, Zhaoming Ye, and co‐workers introduce a strategy of precise photothermal therapy for highly heterogenous cancers by a tumor‐customized 2D supramolecular nanodisc (T‐ND). By modifying Cy7‐TCF crystal with phage display derived tumor‐customized binding peptides, T‐ND shows excellent photothermal efficacy to ablate the tumor and achieves ultralong retention time of more than 24 days in the "off‐target" tumor site.